No colonization resistance to Campylobacter jejuni in broilers fed brown algal extract-supplemented diets - Eliasson, Eliška; Sun, Li; Cervin, Gunnar; Pavia, Henrik; Tällberg, Gustav; Ellström, Patrik; Ivarsson, Emma (Frontiers in Microbiology, 2024)
Campylobacter jejuni gastroenteritis is the most commonly reported zoonosis within the EU, with poultry products regarded as the primary source of transmission to humans. Therefore, finding strategies to reduce Campylobacter colonization in broilers holds importance for public health. Recent studies suggest that supplementation of broiler feed with brown algal extracts, particularly laminarin, can provide beneficial effects on broiler gut health, growth performance, and gut microbiota. However, its effect on gut microbiota development and subsequent reduction of Campylobacter loads in broiler caeca during the later stages of the birds' lives remains unclear. Methods: Experimental colonization of Ross 308 broilers with two different strains of C. jejuni was conducted, with groups fed either a basal diet or the same basal diet supplemented with 725 ppm algal extract from Saccharina latissima to provide 290 ppm laminarin. Fecal samples were collected for bacterial enumeration, and caecal samples were obtained before and after the C. jejuni challenge for the determination of microbiota development. Results and discussion: No significant differences in fecal C. jejuni concentrations between the groups fed different diets or exposed to different C. jejuni strains were observed. This suggests that both strains colonized the birds equally well and that the laminarin rich algal extract did not have any inhibitory effect on C. jejuni colonization. Notably, 16S rRNA amplicon sequencing revealed detailed data on the caecal microbiota development, likely influenced by both bird age and C. jejuni colonization, which can be valuable for further development of broiler feed formulations aimed at promoting gut health.